Industrial Crystallization : Fundamentals and Applications - Lewis, Alison; Seckler, Marcelo; Kramer, Herman; van Rosmalen, Gerda (Cambridge : Cambridge University Press, 2015)
Bridging the gap between theory and practice, this text provides the reader with a comprehensive overview of industrial crystallization. Newcomers will learn all of the most important topics in industrial crystallization, from key concepts and basic theory to industrial practices. Topics covered include the characterization of a crystalline product and the basic process design for crystallization, as well as batch crystallization, measurement techniques, and details on precipitation, melt crystallization and polymorphism. Each chapter begins with an introduction explaining the importance of the topic, and is supported by homework problems and worked examples. Real world case studies are also provided, as well as new industry-relevant information, making this is an ideal resource for industry practitioners, students, and researchers in the fields of industrial crystallization, separation processes, particle synthesis, and particle technology.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Crystal growth; Chemistry, Technical; Chemical engineering